2014
DOI: 10.1016/b978-0-12-800092-2.00007-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Regulation of Endothelial Barrier Function in Cancer

Abstract: Vascular integrity or the maintenance of blood vessel continuity is a fundamental process regulated by endothelial cell–cell junctions. Defects in endothelial barrier function are an initiating factor in several disease processes including tumor angiogenesis and metastasis. The glycosaminoglycan, hyaluronan (HA), maintains vascular integrity through specific mechanisms including HA-binding protein signaling in caveolin-enriched microdomains, a subset of lipid rafts. Certain disease states, including cancer, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 111 publications
(159 reference statements)
2
52
0
Order By: Relevance
“…Thus, the angiogenic properties of LMW-HA and HMW-HA may vary depending on the composition of the microenvironment. Nevertheless, a high HA expression was shown to correlate with increased angiogenesis and poor prognosis [212] and the assessment of this molecule may represent an important mean for the development of new prognostic tools [199]. …”
Section: Hyaluronan: Not Only a Mere Gluementioning
confidence: 99%
“…Thus, the angiogenic properties of LMW-HA and HMW-HA may vary depending on the composition of the microenvironment. Nevertheless, a high HA expression was shown to correlate with increased angiogenesis and poor prognosis [212] and the assessment of this molecule may represent an important mean for the development of new prognostic tools [199]. …”
Section: Hyaluronan: Not Only a Mere Gluementioning
confidence: 99%
“…Besides "true" PGs, hyaluronan (HA), a non-sulfated glycosaminoglycan that is never covalently linked to a protein core, is capable of evoking a danger signal in response to injury following partial enzymatic cleavage by hyaluronidases (23). The resulting low molecular weight (LMW)-HA fragments accumulate and stimulate TLR2/4 and inflammatory gene expression, thereby promoting angiogenesis and cancer metastasis (7,23,24). Furthermore, active heparan sulfate (HS) fragments generated by heparanase-1 from extracellular barriers (25) and HS proteoglycan sources, such as the basement membrane perlecan (26), the cell surface syndecans (27), and glypicans (28), serve as TLR4-interacting DAMPs (29,30) (Fig.…”
Section: Damps Derived From the Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…19 Studies have indicated that impairment of blood vascular barrier could be mediated by LMW-HA and an accelerating vascular metastasis of cancer cells was followed. 20,21 To date, there are no reports regarding how LMW-HA modulates lymphatic endothelial cell junctions or facilitates cancer cell metastasis through lymph vessels. As lymphatic vascular endothelial cells are similar to blood vessels in terms of their proliferation behavior and HA receptor expression patterns, it is reasonable to assume that LMW-HA regulates lymphatic endothelial intercellular adhesion by binding to lymphatic endothelial hyaluronan receptor-1 (LYVE-1) and thus accelerates tumor cell migration into the lumen of lymphatic vessels.…”
Section: Introductionmentioning
confidence: 99%